Acceptance of Children with Special Needs in Inclusive Settings Through Ecological System Theory - Faatinisa, Esty; Rochyadi, Endang; Hufad, Achmad; Aprilia, Imas Diana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
Parental acceptance of children with special needs is a crucial component in the success of inclusive early childhood education. This study aims to explore the factors influencing the acceptance process using Bronfenbrenner’s ecological systems theory. A qualitative case study approach was employed, involving three mothers of children with Autism Spectrum Disorder (ASD) enrolled in an inclusive playgroup at Nurul Jannah, Bandung. Data were collected through in-depth interviews, observation, and documentation, then analyzed using inductive thematic analysis following Braun and Clarke's procedures. The findings reveal that family pressure, marital conflict, and emotional fatigue hinder the acceptance process. In contrast, strong support from the nuclear family fosters faster acceptance and proactive involvement in therapy and education. Interactions within the family microsystem appear to be the most influential factor in shaping parental responses. These results suggest that parental acceptance is not merely a personal matter but a product of complex social dynamics within ecological systems. Therefore, intervention strategies must be systemic, involving both family and broader social environments. The study recommends future research to examine the roles of mesosystem and macrosystem actors, and to apply longitudinal approaches to observe changes in parental acceptance over time.